Examining the Indonesia FATF Membership to Combat Money Laundering in Natural Resources Sector - Gisela Keyla; Auralia Rizki Putri (Business and Human Rights Law & Policy, 2025)
The aim of this study is to shed light on Indonesia's decision to become a full member of the Financial Action Task Force (FATF) and examine its impact on money laundering within the country's mining, forestry, and fishery sectors. The research follows a deductive approach, attempting to respond to the question: How does full FATF membership contribute to eradicating money laundering in Indonesia's mining, forestry, and fishery sectors? This article employs doctrinal legal research method, which analyzes and interprets existing rules, principles, and case law. The paper finds that FATF membership is advantageous for Indonesia, as it helps address the gaps and challenges the country faces in tackling money laundering in the natural resources sector. Specifically, it addresses Indonesia’s struggles in mutual legal assistance in extradition and asset confiscation, beneficial owner tracking, regional and international financial sector collaboration, and other internal issues. Furthermore, FATF membership demonstrates Indonesia's strengthened commitment to tackling money laundering in the natural resources sectors.